Bypassing industrial development - Batalla, Eric Vincent C. (Animo Repository, 2018)
Once called the Sick Man of Asia, the Philippines has recently gained a respectable record of economic performance. On the surface, the economic situation in the mid-2010s is far better than that of two or three decades ago. Both by design and accident, the country has “leapfrogged” industrial development and weathered external and domestic shocks with relative success. However, the Philippines is still beset with serious problems of poverty, income inequality, and unemployment/underemployment. Likewise, governance issues such as corruption, regulatory capture, and the lack of observance of the rule of law continue to obstruct the path to progress. This chapter, which provides a brief overview of the contemporary Philippine economy, is divided into three sections. The first revisits the 1980s, a critical period in the country’s economic history. The second outlines major institutional reforms and how they contributed to contemporary economic performance. The third and final section presents the Philippines as a consumption-driven, service-oriented economy in need of diversification in order to accelerate and sustain economic growth and development. © 2018 selection and editorial matter, Mark R. Thompson and Eric Vincent C. Batalla; individual chapters, the contributors.